Blockchain for Beginners: It's touted as a Link to the future of journalism. The first step is trying to understand what it is. - MORRIS, ANGELA (Quill)
The article offers information on blockchain technology and cryptocurrency which are considered as links to the future of journalism. Topics covered include their potential of adding new revenue streams for journalism, the ability of blockchain technology to create more security and permanence of news archives, and the technology's potential of giving readers a new way to engage with news and journalists.